Spinal cord α-synuclein deposition associated with myoclonus in patients with MSA-C. (13th August 2019) - Hwang, Jaeho; Bank, Anna M.; Mortazavi, Farzad; Oakley, Derek H.; Frosch, Matthew P.; Schmahmann, Jeremy D.
Abstract : Objective: To test the hypothesis that myoclonus in patients with multiple system atrophy with predominant cerebellar ataxia (MSA-C) is associated with a heavier burden of α-synuclein deposition in the motor regions of the spinal cord, we compared the degree of α-synuclein deposition in spinal cords of 3 patients with MSA-C with myoclonus and 3 without myoclonus. Methods: All human tissue was obtained by the Massachusetts General Hospital Department of Pathology with support from and according to neuropathology guidelines of the Massachusetts Alzheimer's Disease Research Center. Tissue was stained with Luxol fast blue and hematoxylin & eosin for morphologic evaluation, and with a mouse monoclonal antibody to α-synuclein and Vectastain DAB kit. Images of the spinal cord sections were digitized using a 10× objective lens. Grayscale versions of these images were transferred to ImageJ software for quantitative analysis of 8 different regions of interest (ROIs) in the spinal cord: dorsal column, anterior white column, left and right dorsal horns, left and right anterior horns, and left and right lateral corticospinal tracts. A mixed-effect, multiple linear regression model was constructed to determine if patients with and without myoclonus had significantly different distributions of α-synuclein deposition across the various ROIs. Results: Patients with myoclonus had more α-synuclein in the anterior horns ( p < 0.001) and lateral corticospinal tracts ( p = 0.02) than those without myoclonus. Conclusions: In MSA-C, myoclonus appears to be associated with a higher burden of α-synuclein deposition within spinal cord motor regions. Future studies with more patients will be needed to confirm these findings.